PEMETAAN KAWASAN BAHAYA BENCANA LONGSOR DI KABUPATEN SOLOK MENGGUNAKAN METODE RANDOM FOREST - Syofiah, Yena Syaidah; Ahyuni, Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
Based on data from the Solok Regency Regional Disaster Management Agency, Solok Regency has experienced landslides spread across 13 sub-districts. Mapping the danger of landslides is needed for disaster management purposes. The Random Forest method can be used to determine the danger of landslides. Landslide records were obtained from field measurements at 101 points, 80% of the total points were used as training data and 20% for testing data. The AUC value obtained was 0.8533, which means the model is good at predicting landslide danger. The most dominant factors influencing the occurrence of landslides based on variable contribution values ​​are slope slope with values ​​(MDA= 58.89, MDG = 19.10), road distance (MDA = 42.47MDG = 9.54), and elevation (MDA = 24.41, MDG = 7.03). The landslide hazard map was reclassified into five hazard level classes obtained from probability values. The danger is very low (21.55%), low (18.81%), medium (24.78%), high (18.69%), and very high (16.18%).